Utilization of Edmodo as an Online Tool in EFL Writing Class to Increase Students’ Writing Ability - M. Zaini Miftah (IAIN Salatiga, 2018)
This article reports the results of investigation on the utilization of Edmodo as an online tool in EFL writing class to increase the students’ ability in producing an argumentative essay. Classroom Action Research was applied in the study. 15 Indonesian EFL students who enrolled in the course of Argumentative Writing became the participants of the study. Observation, writing task, questionnaire, and field notes were used for the data collection. The data obtained were categorized into qualitative and quantitative data. The collected data were then analyzed for the conclusion drawn. The results show that the utilization of Edmodo in EFL writing class could significantly increase the students’ ability in producing an argumentative essay in the Cycle 2. The Appropriate teaching procedures are; prepare the teaching materials, introduce Edmodo, guide students to get ready to use Edmodo, give an opportunity to students to get in the Edmodo group, train students to use Edmodo group, group students in the small group via Edmodo, give students writing tasks through Edmodo, provide a guideline and tell students to follow the guideline to access their small group, ask students to post their first drafts of an argumentative essay on their small groups, ask students to give feedback on their peers’ works, ask students to revise their drafts of the argumentative essay based on the their peers’ feedback and teacher, and ask students to post their final products of an argumentative essay on their Edmodo account.Keywords: Edmodo; Online tool, EFL writing class, Writing ability, Argumentative essay